The effects of feeding immunostimulant β-glucan on the immune response of Pangasianodon hypophthalmus - Wanna Sirimanapong (2018)
© 2015 Elsevier Ltd. Immunostimulants are food additives used by the aquaculture industry to enhance the immune response of fish, and although β-glucans are now commonly used for this purpose in aquaculture, little is known about their effects on the immune response of Pangasianodon hypophthalmus. Thus, a variety of immune parameters (e.g. phagocytosis, respiratory burst, lysozyme, complement, peroxidase, total protein, total anti-protease, total IgM, natural antibody titres, and specific IgM titres) was examined in this species after feeding fish with a basal control diet or diets supplemented with 0.05, 0.1, or 0.2g/kg fungal-derived β-glucan or 0.1% commercial yeast-derived β-glucan, as a positive control diet, for a period of four weeks. The effect of the glucans on disease resistance was then evaluated by experimentally infecting the fish with Edwardsiella ictaluri by immersion and mortalities monitored for 14 days. Samples were collected from fish for analysis at 0, 1, 3, 7, 14, 21 and 28 days post-feeding (dpf), and also at 14 days post infection (dpi). The lowest dose of fungal-derived β-glucan (0.05%) appeared insufficient to effectively stimulate the immune response of the fish, while those fed with the two highest levels of fungal-derived β-glucan had enhanced immune responses compared to the control group. Significantly elevated levels of respiratory burst activity on all days examined (. P<0.05) and lysozyme activity on 7dpf were found in the group fed 0.2% fungal-derived β-glucan, while plasma anti-protease activity was significantly enhanced (. P<0.05) by 21dpf, natural antibody titres by 3dpf and complement activity by 7dpf and also at 14dpi in the group fed 0.1% fungal-derived β-glucan. No statistical differences was seen in the level of mortalities between the dietary groups, although the group fed with the control diet had the highest level of mortalities and the groups fed with commercial yeast-derived β-glucan and 0.2% fungal-derived β-glucan the lowest. •The immune response of Pangasianodon hypophthalmus, or striped catfish, was examined.•Immunostimulant diets containing β-glucan were fed to striped catfish.•The immunostimulatory role of β-glucan on striped catfish immunity was studied.•Difference levels of β-glucan in the diets of striped catfish were evaluated.•β-glucan supplemented diet stimulated the immune response of striped catfish.